The Theory of the Firm goes Global - Dalia Marin (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2012)
What insights can be gained from bringing the theory of the firm to the global economy? I discuss several new features of the world economy that can be explained by incorporating the theory of the firm into the theory of international trade. Among the new features I discuss are the move to flatter corporate hierarchies and the decentralization of authority in firms, the “war for talent”, the rise of CEO pay in rich countries, organizational convergence across countries, and firm heterogeneity.
urn:nbn:de:bvb:19-epub-12690-0
Keywords: F23; D21; L22; 330; International Trade and Organizations; Firm heterogeneity; Organizational convergence; Decentralization in the firm; The rise of CEO pay; Theorie der Unternehmung; Globalisierung; Internationale Wirtschaft; Außenwirtschaftstheorie; Organisatorischer Wandel; Managervergütung; Theorie